Communicating with Local Elected Officials - Ricky W. Telg; Shelli Rampold (EDIS, 2018)
This EDIS document is part of a series on communicating with elected officials. Elected officials at the local, state, and national levels create policies and laws that can impact the agricultural and natural resources (ANR) sector in Florida. This publication (a) discusses how county commissioners prepare to vote on ANR policies, (b) identifies factors that impact county commissioners’ decision-making about ANR policy decisions, (c) identifies sources county commissioners’ use to gather ANR information, and (d) discusses how information from Extension faculty and other individuals can be presented to effectively inform elected officials on important ANR topics, explain complex processes, and educate them about Extension programs.